Identification of acquired somatic mutations in the gene encoding chromatin-remodeling factor ATRX in the alpha-thalassemia myelodysplasia syndrome (ATMDS). - Gibbons, R; Pellagatti, A; Garrick, D; Wood, W; Malik, N; Ayyub, H; Langford, C; Boultwood, J; Wainscoat, J; Higgs, D (2003)
Inherited mutations of specific genes have elucidated the normal roles of the proteins they encode by relating specific mutations to particular phenotypes. But many potentially informative mutations in such genes are lethal early in development. Consequently, inherited mutations may not reflect all the functional roles of such proteins. Acquired, somatic defects should reflect a wider spectrum of mutations because they are not prone to negative selection in development. It has been difficult to identify such mutations so far, but microarray analysis provides a new opportunity to do so. Using this approach, we have shown that in individuals with myelodysplasia associated with alpha-thalassemia (ATMDS), somatic mutations of the gene encoding the chromatin remodeling factor ATRX cause an unexpectedly severe hematological phenotype compared with the wide spectrum of inherited mutations affecting this gene. These findings cast new light on this pleiotropic cofactor, which appears to be an essential component rather than a mere facilitator of globin gene expression.